Implementasi Strategi Augmented Product Dan Atribut Produk Sepeda Motor Merek Honda Dalam Menciptakan Kepuasan Konsumen - Tri Palupi Robustin (JURNAL MANAJEMEN DAN BISNIS INDONESIA, 2021)
This study aims to determine the influence of retail service quality: (1) Whether augmented products affect consumer satisfaction; (2) Do product attributes affect consumer satisfaction; (3) Do augmented products and product attributes simultaneously affect consumer satisfaction. The research population is consumers who buy Honda brand motorcycles domiciled in Puger Subdistrict, with a sample number of 60 respondents. Data analysis techniques use multiple regression analysis with SPSS version 17 programs. The results showed that: (1)There is an influence of augmented products on consumer satisfaction. The results of this study mean that the better augmented products provided by Honda brand motorcycles, it will increase consumer satisfaction; (2) There is an influence of product attributes on customer satisfaction. The results of this study mean that the better product attributes consisting of quality, features, style and design provided by Honda brand motorcycles, it will increase consumer satisfaction; (3) There is a simultaneous influence of augmented products and product attributes on consumer satisfaction.